2022
DOI: 10.53400/mimbar-sd.v9i1.40762
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Effectiveness of Students’ Punishment by Teachers in Osun State, Nigeria

Abstract: Anti-social behaviors among Nigerian in-school adolescents continue to increase in an alarming rate. This study assessed teachers’ perceived effectiveness of punishment on student by in Osun State, Nigeria. Participants’ age and years of teaching experience were examined. The research design employed in this study was survey with a population of 200 teachers as the participants. For data collection, a questionnaire designed by the researcher was administered. Percentage, t-test and Analysis of Variance (ANOVA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Phungphai & Boonmoh (2021) found that incentives given to students during the teachinglearning process significantly improve the feeling of enjoyment and excitement among learners for selfdevelopment and showing positive behavior. Okesina & Famolu (2022) proved that it is required to have teachers training in punishing as it affects the teaching and learning process if properly utilized to enhance teaching experiences. Turley and Graham (2019) found in their studies that students who received feedback on their performance enhanced learning habits, responses to different tasks, and enthusiasm as it develops the interaction between teacher and students.…”
Section: Introductionmentioning
confidence: 99%
“…Phungphai & Boonmoh (2021) found that incentives given to students during the teachinglearning process significantly improve the feeling of enjoyment and excitement among learners for selfdevelopment and showing positive behavior. Okesina & Famolu (2022) proved that it is required to have teachers training in punishing as it affects the teaching and learning process if properly utilized to enhance teaching experiences. Turley and Graham (2019) found in their studies that students who received feedback on their performance enhanced learning habits, responses to different tasks, and enthusiasm as it develops the interaction between teacher and students.…”
Section: Introductionmentioning
confidence: 99%